2022
DOI: 10.26803/ijlter.21.5.18
|View full text |Cite
|
Sign up to set email alerts
|

Revitalizing the Oddi Continuing Learning Inventory

Abstract: The Oddi Continuing Learning Inventory (OCLI) is one of the most popular instruments for measuring self-directed learning (SDL). Although several previous studies have validated it, an exploratory application of confirmatory factor analysis had not been attempted; such an analysis provided new insights. Responses from 159 students from Aalborg University, a Problem-Based Learning institution known for its high degree of self-directed project work, were analyzed. This investigation examines all previously sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 18 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…The study ultimately found that the OCLI can be applied to gain instights into SDL in a context such as AAU PBL with certain limitations in mind, as elaborated in paper 1 (Clausen & Hansen, 2022). Findings indicate that the OCLI measures stable underlying dimensions related to SDL and that the methodology applied to revalidate it could advantageously be used to revitalize other instruments of similar potential.…”
Section: Construction Engineering 77mentioning
confidence: 89%
See 4 more Smart Citations
“…The study ultimately found that the OCLI can be applied to gain instights into SDL in a context such as AAU PBL with certain limitations in mind, as elaborated in paper 1 (Clausen & Hansen, 2022). Findings indicate that the OCLI measures stable underlying dimensions related to SDL and that the methodology applied to revalidate it could advantageously be used to revitalize other instruments of similar potential.…”
Section: Construction Engineering 77mentioning
confidence: 89%
“…Chapter 3 outlines the process of revalidating the Oddi Continuing Learning Inventory (OCLI), an instrument designed to assess an individual's inclination towards self-direction in learning. This effort takes aim at answering the first subordinate research question and the results are also reported in paper 1 (Clausen & Hansen, 2022). The chapter further elaborates on the review of prior validation studies pertaining to the OCLI present in the paper.…”
Section: Outline Of the Thesismentioning
confidence: 99%
See 3 more Smart Citations